Programming style and teaching internationalisation of programms - Dagys, Viktoras; Grigas, Gintautas (Lietuvos matematikos rinkinys, 2010)
The possibilities to introduce school students to software internationalization element are discussed. The basic knowledge of internalization can be provided in the forma of simple practical tasks of programming. The software internalization learning is a multi-topic: students gain understanding of internationalization and localization of programs, enough knowledge to be able to test actually used programs, especially open source software (this could be a serious motivation), they learn about the world’s linguistic diversity, realize deeper meaning of native language and its place among the other languages.
Keywords: teaching programming; software internationalisation; software lokalisation; programming style